Design of a Web-Based Hazard E-Report Application Using the Laravel Framework at Surabaya Aviation Polytechnic - Cascadia, Lydia; Suprapto, Yuyun; Rochmawati, Laila (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Surabaya Aviation Polytechnic is a vocational higher education institution equipped with various facilities such as classrooms, laboratories, and dormitories to support the academic and non-academic activities of cadets. However, the current manual reporting system for facility damage poses several problems, including delays in handling, lack of centralized documentation, and limited transparency in report status. To address these issues, this study aims to design and develop a web-based e-report hazard application using the Laravel framework. The study adopts the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model as a systematic approach. The system design uses the Unified Modeling Language (UML), while the application evaluation is conducted using the User Experience Questionnaire (UEQ). The application is developed using the PHP programming language and tested based on user feedback. The result is a web application that allows cadets to submit hazard reports accompanied by photo/video evidence, with automatic notifications sent to hazard officers (PJ Hazard) and dormitory supervisors. Additionally, the system enables users to track the status of repairs and facilitates audits by relevant authorities. Based on the evaluation results, the application has proven to be effective and efficient in improving the speed and transparency of the reporting process. Therefore, this application is expected to be implemented.